THE ASSOCIATION BETWEEN FAMILY SUPPORT AND PHYSICAL ACTIVITY ENGAGEMENT IN TYPE 2 DIABETES PATIENTS AT PRIMARY CARE LEVEL - Iswatun Iswatun; Endah Sri Wijayanti; Khotibul Umam; Joko Susanto; Anih Kurnia; Jabarul Ikrom Rahmantara (Universitas Airlangga, 2026)
Introduction: Diabetes Mellitus (DM), often referred to as the silent killer, is one of the most common chronic diseases. Type 2 Diabetes Mellitus is characterized by insulin resistance. Physical activity can reduce the risk of complications in patients with type 2 diabetes mellitus. Family support plays a crucial role in enhancing patients’ engagement in physical activity. This study aimed to analyze the relationship between family support and physical activity engagement among patients with type 2 diabetes mellitus at the Deket Health Center, Lamongan Regency. Methods: This study employed a correlational quantitative design with a cross-sectional approach. The research was conducted in March 2023. The population consisted of 59 patients with type 2 diabetes mellitus, with a sample of 51 respondents selected using a consecutive sampling technique. The independent and dependent variables were family support and physical activity, respectively. Data were collected using a family support questionnaire and the Global Physical Activity Questionnaire (GPAQ), which consists of 16 items (P1–P16). Data were analyzed using the Spearman correlation test. Results: The findings indicated that most respondents had good family support and engaged in high levels of physical activity. The Spearman correlation test showed a value of r = 0.574 (indicating a strong relationship) and p = 0.000 (p ≤ 0.05). Conclusions: There is a significant relationship between family support and physical activity engagement among patients with type 2 diabetes mellitus at the Deket Health Center, Lamongan Regency. It is recommended that patients with type 2 diabetes mellitus increase their level of physical activity.